Assistantship improves medical students' perception of their preparedness for starting work. (2nd January 2016) - Braniff, Conor; Spence, Roy A.; Stevenson, Mike; Boohan, Mairead; Watson, Peter
Abstract: Background: The GMC has recommended introducing student assistantships during which final year students, under supervision, undertake most of the responsibilities of a FY1 doctor. The Medical School at Queen's University Belfast in 2011/12 introduced an assistantship programme. We have evaluated the impact of the assistantship on students' perception of their preparedness for starting work. Methods: Students were asked to complete a questionnaire at the beginning of the assistantship. It assessed the students' perception of their preparedness in five areas: clinical and practical skills, communications skills, teaching and learning, understanding the work environment and team working. After the assistantship they again completed the questionnaire. Comparison of the results allowed an assessment of the impact of the assistantship. Results: There was a statistically significant improvement in the students' perception of their preparation for 49 of 56 tasks contained within the questionnaire. After the assistantship 81.2% of students felt well prepared for starting work compared with 38.9% before the assistantship. 93.9% agreed that the assistantship had improved their preparedness for starting work. Conclusions: The assistantship at Queen's University improves medical students' perception of their preparedness for starting work. The majority of medical students feel well prepared for starting work after completing the assistantship.